The Tie2 receptor antagonist angiopoietin 2 facilitates vascular inflammation in systemic lupus erythematosus. Issue 10 (17th October 2008) - Kümpers, P; David, S; Haubitz, M; Hellpap, J; Horn, R; Bröcker, V; Schiffer, M; Haller, H; Witte, T
Abstract : Objective: To investigate the role of the angiopoietin–tyrosine kinase with Ig-like and epidermal growth factor-like domains (Ang–Tie) system in systemic lupus erythematosus (SLE). Endothelial activation is emerging as a key event for leukocyte recruitment and accelerated atherosclerosis in SLE. Recently, the endothelial-specific Ang–Tie ligand–receptor system has been identified as a major regulator of vascular responsiveness to inflammatory stimuli. Methods: Ang1 (by immunoradiometric sandwich assay (IRMA)) and Ang2 (by ELISA) were measured in sera of 43 patients with SLE and 30 healthy controls. Expression of Ang2 was studied by immunohistochemistry in biopsies of human lupus nephritis. Results: Circulating Ang2 concentrations were increased and concentrations of Ang1 decreased in patients with active SLE compared to healthy controls. This tendency was still present in inactive SLE, although less pronounced. Individual Ang2 concentrations correlated well with SLE Disease Activity Index (SLEDAI) score, proteinuria, double-stranded DNA (dsDNA) titre and soluble vascular cell adhesion molecule 1 (sVCAM-1). In a multivariate regression analysis, renal involvement was the only independent predictor for elevated Ang2. Serum Ang2 was identified as a strong predictor for disease activity by receiver operating characteristic (ROC) procedures and regression tree models. Protein expression of Ang2 was upregulated in glomeruli of patients with lupus nephritis. Conclusions: These data indicate that Ang2-mediated disruption of protective Ang1/Tie2 signalling is operational in SLE. Ang2 might facilitate endothelial inflammation, permeability and contribute to premature atherosclerosis. Furthermore, circulating Ang2 may be a valuable new biomarker for disease activity in SLE. Strategies to control the deleterious effects of Ang2 may open new perspectives to prevent endothelial inflammation in SLE.